2021
DOI: 10.1186/s12903-021-01577-1
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of seeking emergency and routine dental care in Saudi Arabia during the COVID-19 pandemic

Abstract: Background Between March and June 2020, closing dental clinics during the COVID-19 pandemic except for emergency dental care was recommended. It is documented that health-seeking behaviors change during pandemics. The objective of this study was to examine social determinants associated with decisions to seek dental care in Saudi Arabia during the COVID-19 pandemic. Methods A total of 4372 participants were invited to this cross-sectional web-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 33 publications
(23 reference statements)
1
37
0
2
Order By: Relevance
“…The respondents were asked to rate the truthfulness of each statement on a Likert scale of four (1 for "not true for me at all", 2 for "somewhat true", 3 for "mostly true", and 4 for "definitely true"). As seeking healthcare was linked to fear and confidence in the level of provided care [25,27], these two items were developed for the purpose of the present study following FIVE format. A group of four dental public health experts approved the appropriateness of the items in estimating fear to seek dental care during the pandemic.…”
Section: Fear To Seek Dental Carementioning
confidence: 99%
See 1 more Smart Citation
“…The respondents were asked to rate the truthfulness of each statement on a Likert scale of four (1 for "not true for me at all", 2 for "somewhat true", 3 for "mostly true", and 4 for "definitely true"). As seeking healthcare was linked to fear and confidence in the level of provided care [25,27], these two items were developed for the purpose of the present study following FIVE format. A group of four dental public health experts approved the appropriateness of the items in estimating fear to seek dental care during the pandemic.…”
Section: Fear To Seek Dental Carementioning
confidence: 99%
“…Failure to seek dental care can negatively impact oral health status. Even though some studies looked into the barriers to dental visits during the pandemic in Saudi Arabia [26][27][28], factors related to higher fear and reluctance to seek dental care were not widely investigated. Considering these factors is essential for targeting these specific populations in preventive dental programs during the current and future pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…The details of each tool, for which the validity and the reliability were tested in previous studies, were discussed in our earlier published studies [27,31]. The K-10, having ten items, was scored based on the responses using a 5-point Likert scale; the scoring was categorized into low (10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21), high (22)(23)(24)(25)(26)(27)(28)(29) and very high . The FCV-19S, having seven items, was scored based on the responses using a 5-point Likert scale; the scoring was categorized into low (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and high (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)…”
Section: Study Questionnairementioning
confidence: 99%
“…During the pandemic, that practice potentially increased the risk of spreading infection at the dentist practice. It has been demonstrated that the virus in the aerosol may survive for more than 3 h, with surface stability over 72 h [ 13 ]. Development of that scientific evidence generated anxiety and stress amongst the students doing their clinical placement.…”
Section: Introductionmentioning
confidence: 99%
“…21 A plethora of published studies has surveyed the knowledge, attitude, and behaviors of DHCP and dental patients during the COVID-19 pandemic. 17,18,[21][22][23][24][25][26][27][28][29][30][31][32] Umeizudike et al reported a positive attitude among Nigerian dental students regarding infection control practices, however, their knowledge was just adequate. 24 Variation in knowledge regarding COVID-19 among Saudi dental professionals was most observed regarding the virus survival and handwashing hygiene practice.…”
Section: Introductionmentioning
confidence: 99%